Intravital damage to the body of Dickinsonia (Metazoa of the late Ediacaran). (November 2020) - Ivantsov, Andrey; Zakrevskaya, Maria; Nagovitsyn, Aleksey; Krasnova, Anna; Bobrovskiy, Ilya; Luzhnaya (Serezhnikova), Ekaterina
Abstract: Several specimens of Dickinsonia cf. D . menneri, originating from a single burial event at the Lyamtsa locality of the late Ediacaran (Vendian) in the southeastern White Sea area, Russia, represent deviations from normal morphology: a reduction in the total length of the body; the loss of portions of the body; various deformations of the transverse elements, called isomers; and splitting of the longitudinal axis with the formation of two posterior ends. It is assumed that these deformations were formed as a result of non-lethal damage, which occurred long before the burial event, and the response of Dickinsonia to them. The progress of the regeneration process at the damaged areas, and especially its deviations, indicates that the growth zone was located at the posterior end of the Dickinsonia body. The cause of non-lethal damage to Dickinsonia could not be established, but the local distribution of deformed specimens preserved in the same burial event alongside cyanobacterial colonies, and the presence of weak deformations, expressed only in shortening of the length of some isomers, lead to the conclusion that damage resulted from short episodes of physicochemical impact, rather than occasional attacks by a hypothetical macrophage.